2022
DOI: 10.3389/fimmu.2022.828665
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mRNA 3′-End Processing and Transcription Termination in Virus-Infected Cells

Abstract: Eukaryotic mRNA 3´-end processing is a multi-step process beginning with pre-mRNA transcript cleavage followed by poly(A) tail addition. Closely coupled to transcription termination, 3´-end processing is a critical step in the regulation of gene expression, and disruption of 3´-end processing is known to affect mature mRNA levels. Various viral proteins interfere with the 3´-end processing machinery, causing read-through transcription and altered levels of mature transcripts through inhibition of cleavage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“… Identified CPA factors implicated in pre-mRNA 3′ end processing. Eukaryotic mRNA 3′ end processing is a multi-step process ( 126 , 127 ). In this study, we identified a variety of CPA factors implicated in multiple steps of 3′ end processing.…”
Section: Resultsmentioning
confidence: 99%
“… Identified CPA factors implicated in pre-mRNA 3′ end processing. Eukaryotic mRNA 3′ end processing is a multi-step process ( 126 , 127 ). In this study, we identified a variety of CPA factors implicated in multiple steps of 3′ end processing.…”
Section: Resultsmentioning
confidence: 99%
“…There is, also, a growing interest in the metabolic remodeling of intercellular matrix proteins, including the action of some cathepsins [514,515]. Recently, as an example of an expansive analysis of our biocenosis, it has been found that some viruses may affect/interfere with the fine-tuned system of selection of mRNAs to be translated into newly formed proteins [516]. (h) Excess of energy-providing nutrients.…”
Section: Cell-related Mechanisms: Bi Biochemical Inflammationmentioning
confidence: 99%
“…RBPs affect every aspect of RNA biology, including pre‐mRNA splicing, RNA methylation modification, translation, and degeneration of mRNA. RBPs not only modulate each of these biological processes but also establish a link between them 14–16 . Therefore, RBPs play a central role in post‐transcriptional gene regulation (PTGR).…”
Section: Introductionmentioning
confidence: 99%
“…RBPs not only modulate each of these biological processes but also establish a link between them. 14 , 15 , 16 Therefore, RBPs play a central role in post‐transcriptional gene regulation (PTGR). The dynamic interaction between RBPs and their RNA targets is mediated with RNA‐binding domains (RBDs) residing exclusively in RBPs.…”
Section: Introductionmentioning
confidence: 99%